Smoothelin-Like Protein 1 Regulates Development and Metabolic Transformation of Skeletal Muscle in Hyperthyroidism - Major, Evelin; Győry, Ferenc; Horváth, Dániel; Keller, Ilka; Tamás, István; Uray, Karen; Fülöp, Péter; Lontay, Beáta (Frontiers in Endocrinology, 2021)
Hyperthyroidism triggers a glycolytic shift in skeletal muscle (SKM) by altering the expression of metabolic proteins, which is often accompanied by peripheral insulin resistance. Our previous results show that smoothelin-like protein 1 (SMTNL1), a transcriptional co-regulator, promotes insulin sensitivity in SKM. Our aim was to elucidate the role of SMTNL1 in SKM under physiological and pathological 3,3′,5-Triiodo-L-thyronine (T3) concentrations. Human hyper- and euthyroid SKM biopsies were used for microarray analysis and proteome profiler arrays. Expression of genes related to energy production, nucleic acid- and lipid metabolism was changed significantly in hyperthyroid samples. The phosphorylation levels and activity of AMPKα2 and JNK were increased by 15% and 23%, respectively, in the hyperthyroid samples compared to control. Moreover, SMTNL1 expression showed a 6-fold decrease in the hyperthyroid samples and in T3-treated C2C12 cells. Physiological and supraphysiological concentrations of T3 were applied on differentiated C2C12 cells upon SMTNL1 overexpression to assess the activity and expression level of the elements of thyroid hormone signaling, insulin signaling and glucose metabolism. Our results demonstrate that SMTNL1 selectively regulated TR expression. T3 excess triggered the development of insulin resistance while overexpression of SMTNL1 induced insulin sensitivity through the inhibition of JNK activity by 30% and hampered the non-genomic effects of T3 by decreasing the activity of ERK1/2 through PKC. SMTNL1 overexpression reduced IRS1 Ser307 and Ser612 phosphorylation by 23% and 34%, respectively, in hyperthyroid model to restore the normal responsiveness of glucose transport to insulin. SMTNL1 regulated glucose phosphorylation and balances glycolysis and glycogen synthesis via the downregulation of hexokinase II by 1.4-fold. Additionally, mitochondrial respiration and glycolysis were measured by SeaHorse analysis to determine cellular metabolic function/phenotype of our model system in real-time. T3 overload strongly increased the rate of acidification and a shift to glycolysis, while SMTNL1 overexpression antagonizes the T3 effects. These lines of evidence suggest that SMTNL1 potentially prevents hyperthyroidism-induced changes in SKM, and it holds great promise as a novel therapeutic target in insulin resistance.